Pengaruh Kepuasan Konsumen dan Citra Merek terhadap Keputusan Pembelian Konsumen Sepeda Motor Merek Yamaha PT. Alfa Scorpii Cabang Bilal Medan - Falio Kristianto; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin Syawaluddin (Universitas Batanghari, 2022)
Consumer satisfaction is a feeling of pleasure or disappointment experienced by a consumer both before making a purchase at the company, when these feelings arise after comparing the performance of the product he gets against his expectations so far for the product. Brand image is also a consumer's assessment of the brand offered in a market whose creation can be formed based on personal experiences obtained by consumers either through hearing the product's reputation or experiencing direct post-purchase on the product. The purchase decision is a stage in the decision-making process through a consideration where the individual carries out an evaluation of the various available options and decides on the best choice of a product from only a few. This research uses quantitative descriptive research. The study used multiple linear regression analysis. The research scale used is a Likert scale. Partially, it was found that the variable of customer satisfaction had a significant effect on the purchasing decisions of PT. Alfa Scorpio, Bilal Medan Branch. Partially, the brand image variable has a significant effect on the purchasing decisions of PT. Alfa Scorpio, Bilal Medan Branch. Simultaneously there is a significant influence between the variables of consumer satisfaction and brand image on purchasing decisions of employees of PT. Alfa Scorpio, Bilal Medan Branch.